The Interaction of Monetary and Macroprudential Policies. (Policy Papers; Policy Paper, 2012)
The recent crisis showed that price stability does not guarantee macroeconomic stability. In several countries, dangerous financial imbalances developed under low inflation and small output gaps. To ensure macroeconomic stability, policy has to include financial stability as an additional objective. But a new objective demands new tools: macroprudential tools that can target specific sources of financial imbalances (something monetary policy is not well suited to do). Effective macroprudential policies (which include a range of constraints on leverage and the composition of balance sheets) could then contain risks ex ante and help build buffers to absorb shocks ex post.